Tracking Quantum Coherence in Polariton Condensates with Time-Resolved Tomography - Lüders, Carolin; Pukrop, Matthias; Barkhausen, Franziska; Rozas, Elena; Schneider, Christian; Höfling, Sven; Sperling, Jan; Schumacher, Stefan; Aßmann, Marc (Physical Review Letters)
Keywords: General Physics and Astronomy

A multi-mode super-fano mechanism for enhanced third harmonic generation in silicon metasurfaces - Hähnel, David; Golla, Christian; Albert, Maximilian; Zentgraf, Thomas; Myroshnychenko, Viktor; Förstner, Jens; Meier, Cedrik (Light: Science & Applications)
We present strong enhancement of third harmonic generation in an amorphous silicon metasurface consisting of elliptical nano resonators. We show that this enhancement originates from a new type of multi-mode Fano mechanism. These ‘Super-Fano’ resonances are investigated numerically in great detail using full-wave simulations. The theoretically predicted behavior of the metasurface is experimentally verified by linear and nonlinear transmission spectroscopy. Moreover, quantitative nonlinear measurements are performed, in which an absolute conversion efficiency as high as ηmax ≈ 2.8 × 10−7 a peak power intensity of 1.2 GW cm−2 is found. Compared to an unpatterned silicon film of the same thickness amplification factors of up to ~900 are demonstrated. Our results pave the way to exploiting a strong Fano-type multi-mode coupling in metasurfaces for high THG in potential applications.
Keywords: tet_topic_meta

Compact Metasurface-Based Optical Pulse-Shaping Device - Geromel, René; Georgi, Philip; Protte, Maximilian; Lei, Shiwei; Bartley, Tim; Huang, Lingling; Zentgraf, Thomas (Nano Letters)
Dispersion is present in every optical setup and is often an undesired effect, especially in nonlinear-optical experiments where ultrashort laser pulses are needed. Typically, bulky pulse compressors consisting of gratings or prisms are used to address this issue by precompensating the dispersion of the optical components. However, these devices are only able to compensate for a part of the dispersion (second-order dispersion). Here, we present a compact pulse-shaping device that uses plasmonic metasurfaces to apply an arbitrarily designed spectral phase delay allowing for a full dispersion control. Furthermore, with specific phase encodings, this device can be used to temporally reshape the incident laser pulses into more complex pulse forms such as a double pulse. We verify the performance of our device by using an SHG-FROG measurement setup together with a retrieval algorithm to extract the dispersion that our device applies to an incident laser pulse.
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

A Pulsed Lidar System With Ultimate Quantum Range Accuracy - Kruse, Stephan; Serino, Laura; Folge, Patrick Fabian; Echeverria Oviedo, Dana; Bhattacharjee, Abhinandan; Stefszky, Michael; Scheytt, J. Christoph; Brecht, Benjamin; Silberhorn, Christine (IEEE Photonics Technology Letters)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Efficient Modeling and Tailoring of Nonlinear Wavefronts in Dielectric Metasurfaces - Hähnel, David; Förstner, Jens; Myroshnychenko, Viktor (ACS Photonics)
Dielectric metasurfaces provide a unique platform for efficient harmonic generation and optical wavefront manipulation at the nanoscale. Tailoring phase and amplitude of a nonlinearly generated wave with a high emission efficiency using resonance-based metasurfaces is a challenging task that often requires state-of-the-art numerical methods. Here, we propose a simple yet effective approach combining a sampling method with a Monte Carlo approach to design the third-harmonic wavefront generated by all-dielectric metasurfaces composed of elliptical silicon nanodisks. Using this approach, we theoretically demonstrate the full nonlinear 2π phase control with a uniform and highest possible amplitude in the considered parameter space, allowing us to design metasurfaces operating as third harmonic beam deflectors capable of steering light into a desired direction with high emission efficiency. The TH beam deflection with a record calculated average conversion efficiency of 1.2 × 10–1 W–2 is achieved. We anticipate that the proposed approach will be widely applied as alternative to commonly used optimization algorithms with higher complexity and implementation effort for the design of metasurfaces with other holographic functionalities.
Keywords: tet_topic_meta

Theoretical analysis of four-wave mixing on semiconductor quantum dot ensembles with quantum light - Rose, Hendrik; Grisard, S.; Trifonov, A. V.; Reichhardt, R.; Reichelt, Matthias; Bayer, M.; Akimov, I. A.; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XXVII)
The nonlinear optical response of an ensemble of semiconductor quantum dots is analyzed by wave-mixing processes, where we focus on four-wave mixing with two incident pulses. Wave-mixing experiments are often described with semiclassical models, where the light is modeled classically and the material quantum mechanically. Here, however, we use a fully quantized model, where the light is given by a quantum state of light. Quantum light involves more degrees of freedom than classical light as e.g., its photon statistics and quantum correlations, which is a promising resource for quantum devices, such as quantum memories. The light-matter interaction is treated with a Jaynes-Cummings type model and the quantum field is given by a single mode since the quantum dots are embedded in a microcavity. We present numerical simulations of the four-wave-mixing response of a homogeneous system for pulse sequences and find a significant dependence of the result on the photon statistics of the incident pulses. The model constitutes a problem with a large state space which arises from the frequency distribution of the transition energies of the inhomogeneously broadened quantum dot ensemble that is coupled with a quantum light mode. Here we approximate the dynamics by summing over individual quantum dot-microcavity systems. Photon echoes arising from the excitation with different quantum states of light are simulated and compared.

Control of the electron dynamics in solid-state high harmonic generation on ultrafast time scales by a polarization-skewed laser pulse - Song, Xiaohong; Yang, Shidong; Wang, Guifang; Lin, Jianpeng; Wang, Liang; Meier, Torsten; Yang, Weifeng (Optics Express)
Since high-order harmonic generation (HHG) from atoms depends sensitively on the polarization of the driving laser field, the polarization gating (PG) technique was developed and applied successfully to generate isolated attosecond pulses from atomic gases. The situation is, however, different in solid-state systems as it has been demonstrated that due to collisions with neighboring atomic cores of the crystal lattice strong HHG can be generated even by elliptically- and circularly-polarized laser fields. Here we apply PG to solid-state systems and find that the conventional PG technique is inefficient for the generation of isolated ultrashort harmonic pulse bursts. In contrast, we demonstrate that a polarization-skewed laser pulse is able to confine the harmonic emission to a time window of less than one-tenth of the laser cycle. This method provides a novel way to control HHG and to generate isolated attosecond pulses in solids.
Keywords: Atomic and Molecular Physics; and Optics

Revealing the nonadiabatic tunneling dynamics in solid-state high harmonic generation - Zuo, Ruixin; Song, Xiaohong; Ben, Shuai; Meier, Torsten; Yang, Weifeng (Physical Review Research)
Keywords: General Physics and Astronomy

Manipulation of nonautonomous nonlinear wave solutions of the generalized coupled Gross–Pitaevskii equations with spin–orbit interaction and weak Raman couplings - Belobo, D. Belobo; Meier, Torsten (Results in Physics)
Keywords: General Physics and Astronomy

Diquat Based Dyes: A New Class of Photoredox Catalysts and Their Use in Aerobic Thiocyanation - Meier, Armin; Badalov, Sabuhi; Biktagirov, Timur; Schmidt, Wolf Gero; Wilhelm, René (Chemistry – A European Journal)
A series of new organic donor–π–acceptor dyes incorporating a diquat moiety as a novel electron-acceptor unit have been synthesized and characterized. The analytical data were supported by DFT calculations. These dyes were explored in the aerobic thiocyanation of indoles and pyrroles. Here they showed a high photocatalytic activity under visible light, giving isolated yields of up to 97 %. In addition, the photocatalytic activity of standalone diquat and methyl viologen through formation of an electron donor acceptor complex is presented.
Keywords: General Chemistry; Catalysis; Organic Chemistry